Physiology and Pathology of the Cerebellum. - Dow, Robert S. (University of Minnesota Press, 1958)
The development of electrical methods of recording activity in the nervous system has greatly augmented our knowledge of cerebellar physiology. Now, for the first time in a single volume, this new information has been related to facts derived from older.